Mass spectrometry-based monitoring of millisecond protein–ligand binding dynamics using an automated microfluidic platform. Issue 9 (24th March 2016) - Cong, Yongzheng; Katipamula, Shanta; Trader, Cameron D.; Orton, Daniel J.; Geng, Tao; Baker, Erin S.; Kelly, Ryan T.
Abstract : We present a novel microfluidic platform that features rapid mixing of protein and ligand solutions, variable incubation times, and an integrated electrospray ionization source for mass spectrometry-based monitoring of protein–ligand binding dynamics. Abstract : Characterizing protein–ligand binding dynamics is crucial for understanding protein function and for developing new therapeutic agents. We present a novel microfluidic platform that features rapid mixing of protein and ligand solutions, variable incubation times, and an integrated electrospray ionization source for mass spectrometry-based monitoring of protein–ligand binding dynamics. This platform offers many advantages, including solution-based binding, label-free detection, automated operation, rapid mixing, and low sample consumption.